2022
DOI: 10.1038/s41598-022-23103-1
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, characterization of glucosamine loaded transfersomes and in vivo evaluation using papain induced arthritis model

Abstract: The aim of current study was to develop the transdermal transfersomes of glucosamine for better drug delivery. Stretch ability and plasticity of transfersomes membranes mitigate the risk of vesicle rupture in the skin and allows the drug carrying transfersome to pass through the epidermis following the natural water gradient. Transdermal delivery of Glucosamine has an advantage over oral route, having greater local concentration and fewer systemic effects. Thin Film Rotary method was use to prepare transfersom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Clinical trials confirmed that glucosamine sulphate, at high doses, is the most active molecule to treat OA pain [ 14 , 15 ]. On the other hand, any current reformulation of GlcN was poorly able to increase drug delivery or efficacy [ 16 ]. The effective dosage is about 2 g/day (or 100 mM), but GlcN was found to induce autophagy both in vitro and in vivo chondrocytes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials confirmed that glucosamine sulphate, at high doses, is the most active molecule to treat OA pain [ 14 , 15 ]. On the other hand, any current reformulation of GlcN was poorly able to increase drug delivery or efficacy [ 16 ]. The effective dosage is about 2 g/day (or 100 mM), but GlcN was found to induce autophagy both in vitro and in vivo chondrocytes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%